Aortic stenosis and cardiovascular risk in patients with Homozygous Familial Hypercholesterolemia: a scoping review (Research, Society and Development, 2022)
Homozygous familial hypercholesterolemia (HoFH) is a hereditary, autosomal and biallelic condition capable of generating high plasma levels of low-density cholesterol (LDL-C). Thus, patients with this pathogenesis are at greater risk for the development of adverse cardiovascular events and for aortic stenosis (AS). The purpose of this text is to discuss the association between AS and cardiovascular risk in patients with HoHF. For this Scope Review, carried out through the PubMed and Science Direct platforms between 2020 and 2022, the descriptors chosen were ''Aortic stenosis'', ''Homozygous Familial Hypercholesterolemia'' and ''Atherosclerosis'', associated with the Boolean operator '' AND''. Inclusion criteria consisted of 1) clinical trials, controlled and randomized trials, reviews and meta-analyses; 2) studies on the association between AS and cardiovascular risk in HoFH 3) studies that evaluated the development of cardiovascular injury due to HoFH, as well as its management, follow-up and treatment and 4) articles in English, Spanish and Portuguese. Exclusion criteria consisted of inadequacies to the topic, case reports, studies with animals, in addition to texts outside the time limit. It was observed that supravalvular aortic stenosis (EASV) represented one of the main conditions associated with HoFH, whether or not associated with acute myocardial infarction, coronary heart disease and stroke. The best way to combine lipid-lowering therapies, as well as genetic screening and follow-up strategies, are still controversial topics, as is the choice of cardioprotective therapies.